KOLABORASI PERGURUAN TINGGI DAN MASYARAKAT DALAM MEWUJUDKAN DESA TANGGAP BENCANA DI DESA PUCANGRO, KECAMATAN KALITENGAH, KABUPATEN LAMONGAN - Yendra Erison; Mahmud Aprian Mabruri; Halimur Rosyid; Alif Firdaus Zamzam; Hendy Setiawan (Yayasan Wayan Marwan Pulungan, 2026)
Pucangro Village in Kalitengah District, Lamongan Regency is an area prone to disasters, especially floods and droughts, due to its location in the lowlands near the Bengawan Solo River. The lack of disaster literacy and emergency response infrastructure in this village is a challenge in efforts to reduce disaster risk. This community service activity aims to build the resilience of Pucangro Village through collaboration between universities and the local community. The method used is a participatory approach based on community empowerment, including risk identification, joint action planning, disaster education, emergency response training, formation of the Disaster Resilient Village Volunteer Forum (FRDTB), as well as preparation of village contingency plan documents. The results of the activity showed a significant increase in community knowledge regarding disaster mitigation (84% of participants experienced an increase in post-test scores ≥30%), the formation of a team of trained active volunteers, and the preparation of contingency plan documents that were ready to be integrated into village development planning. This collaboration has proven effective in strengthening local capacity in building a community-based emergency response system.